Literature, Criticism, and Historical Imagination: The Literary Challenge of Hayden White and Dominick LaCapra - Kramer, Loyd S. (Sociologija. Mintis ir veiksmas, 1997)
Translation: Kramer, Loyd S. 1989. Literature, Critisism, and Historical Imagination: The Literary Challenge of Hayden White and Dominick LaCapra. In: The New Cultural History, Berkeley, Los Angeles, London: University of California Press; 97-128.